2010
DOI: 10.1111/j.1532-5415.2010.03161.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mental Health of Homebound Older Adults: An Overlooked Population

Abstract: There are currently more than 38.9 million people over the age of 65 in the United States. Up to 3.6 million of these people are considered housebound and in need of home-based care. Although homebound status is not defined specifically, with a broad range of disability levels, it is evident that people who are homebound suffer from a multitude of medical and psychiatric illnesses. This review examines the current literature to identify the specific physical and psychiatric factors most responsible for the eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
280
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 232 publications
(293 citation statements)
references
References 39 publications
8
280
0
5
Order By: Relevance
“…[19][20][21][22] The comparisons between the results with previous research are complicated due to the considerable differences in the study populations and the heterogeneity of the definitions of homebound status. 6 Not surprisingly, increasing age was significantly associated with being a homebound person, consistent with previous research conducted with older people. 1,4,9,13 Regarding mobility skills, the multivariate analysis showed that independence in walking activity is a crucial element in the task of going outside.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…[19][20][21][22] The comparisons between the results with previous research are complicated due to the considerable differences in the study populations and the heterogeneity of the definitions of homebound status. 6 Not surprisingly, increasing age was significantly associated with being a homebound person, consistent with previous research conducted with older people. 1,4,9,13 Regarding mobility skills, the multivariate analysis showed that independence in walking activity is a crucial element in the task of going outside.…”
Section: Discussionsupporting
confidence: 88%
“…6,17 However, this study focused on people who remained inside the home during the previous week. The findings showed that the homebound status was a highly prevalent problem in the study population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations